Integrated Water Resources Management in View of Environmental Sustainability Aspects - Dr. Mohamad Ali Fulazzaky; Dr. Sutardi (Penerbit UTHM, 2008)
Integrated Water Resources Management (IWRM) in view of environmental sustainability aspects is geared toward readers of decision-makers level taking an introductory to peer the profound problems on water resources and environment. Integrated management means that all the different uses of water resources are considered together. The basis of IWRM is that different uses of water are interdependent. Water allocations and management decisions consider the effects of each use on the others. They are able to take account of overall social and economic goals, including the achievement of sustainable development. The book’s material is also applicable for readers enrolled in upper level science, technology and engineering related to water resources and environment. The readers should already understand such water supply, wastewater, irrigation, water and food production, water and natural disaster, industrial water consumption, cooling water, hydropower energy, and river transportation as well as environmental sustainability.